Quality Feasibility Analysis on the Tapioca Flour Processed from Dried Cassava (The Effect of Dried Cassava Origin and Calcium Hypochlorite Concentration Used) - Wijana, Susinggih; Nurika, Irnia; Habibah, Elina (Jurnal Teknologi Pertanian, 2009)
The aim of this study was to evaluate the quality of tapioca flour processed from dried cassava from many regencies and calcium hypochlorite concentration added. The factorial experimental was done by Randomized Block Design and used three replications.  The dried cassava used from three regencies (Malang, Blitar and Trenggalek) and concentration of calcium hypochlorite included 4 levels (500, 1000, 1500 and 2000 ppm).  The analysis covered color measurement, moisture content, starch content, yield, chlorine residue, and ash content of the  tapioca flour. The results showed that concentration of calcium hypochlorite significantly affected the color, ash content, moisture content and chlorine residue. Whereas the origin area of dried cassava significantly affected on the yield, starch content, moisture content, ash content, and color of tapioka flour. The best treatment was obtained by application of calcium hypochlorite concentration of 500 ppm and the dried cassava from Malang. At this treatment product yielded  achieve 64.83%, moisture content 9,69%, starch content 74.85%, ash content 0.80%, color brightness (L*) 98.24 and chlorine residue on the tapioca flour  33.33 ppm.Keywords: tapioca flour, calcium hypochlorite, dried cassava